Character portraits - Moses, Brian 1950- (England : Longman, 1998)
whether it's the images created by illustrators or the pictures authors paint with their words, this book describes a host of colourful characters.
K-3.
Keywords: Characters and characteristics in literature -- Juvenile fiction; English literature -- 19th century